Strength and hypertrophy responses to constant and decreasing rest intervals in trained men using creatine supplementation - Fleck Steven J; Leite Richard D; Bloomer Richard; Willardson Jeffrey M; Souza-Junior Tácito P; Oliveira Paulo R; Simão Roberto (Taylor & Francis Group, 2011)
Abstract Background The purpose of the current study was to compare strength and hypertrophy responses to resistance training programs that instituted constant rest intervals (CI) and decreasing rest intervals (DI) between sets over the course of eight weeks by trained men who supplemented with creatine monohydrate (CR). Methods Twenty-two recreationally trained men were randomly assigned to a CI group (n = 11; 22.3 ± 1 years; 77.7 ± 5.4 kg; 180 ± 2.2 cm) or a DI group (n = 11; 22 ± 2.5 years; 75.8 ± 4.9 kg; 178.8 ± 3.4 cm). Subjects in both groups supplemented with CR; the only difference between groups was the rest interval instituted between sets; the CI group used 2 minutes rest intervals between sets and exercises for the entire 8-weeks of training, while the DI group started with a 2 minute rest interval the first two weeks; after which the rest interval between sets was decreased 15 seconds per week (i.e. 2 minutes decreasing to 30 seconds between sets). Pre- and post-intervention maximal strength for the free weight back squat and bench press exercises and isokinetic peak torque were assessed for the knee extensors and flexors. Additionally, muscle cross-sectional area (CSA) of the right thigh and upper arm was measured using magnetic resonance imaging. Results Both groups demonstrated significant increases in back squat and bench press maximal strength, knee extensor and flexor isokinetic peak torque, and upper arm and right thigh CSA from pre- to post-training (p ≤ 0.0001); however, there were no significant differences between groups for any of these variables. The total volume for the bench press and back squat were significantly greater for CI group versus the DI group. Conclusions We report that the combination of CR supplementation and resistance training can increase muscular strength, isokinetic peak torque, and muscle CSA, irrespective of the rest interval length between sets. Because the volume of training was greater for the CI group versus the DI group, yet strength gains were similar, the creatine supplementation appeared to bolster adaptations for the DI group, even in the presence of significantly less volume. However, further research is needed with the inclusion of a control group not receiving supplementation combined and resistance training with decreasing rest intervals to further elucidate such hypotheses.